Development of an improved image analysis for optical-based AC electrokinetics data / Adilah Hashim - Adilah, Hashim (2012)
The availability of dielectrophoresis (DEP) method which apart of AC Electrokinetics for cell separation and manipulation are currently becoming highly purposeful due to its function variation and becoming possible. Commonly used in cancer cell detection and drug screening assessment, DEP are able to manipulate polarisable particles with the application of non-uniform electric considering the fact that movement will be induced onto the polarisable particles when placed in the electric fields. The application of DEP are used to be restricted in research for academic prospects only, rather than in manufacturing applications due to the image analyzing processes involved. Thus, this project aims to develop of an improved image analysis for optical based AC Electrokinetics data, which consists of image processing for purpose of development process. In order to perform a process, various image processing techniques have been applied on images that have been given from AC Electrokinetics data. The images are processed with various image processing techniques such as contrast enhancement and image segmentation. There are four contrast enhancement techniques. After that, the image is segmented by applying the image segmentation. The combination between contrast enhancement and image segmentation hopefully will giving a good result. Overall, the development of an image analysis for optical-based AC Electrokinetics data that has been developed. The development that provides an efficient alternative in analyzing the images.